An Ethnographic Study of Yakan Oral Tradition in Southern Philippines: Perspectives from the Community - Saddam Pacio (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the perspectives of the Yakan community on their oral tradition, exploring how it is valued, transmitted, and sustained in the face of changes in social and cultural practices. Through interviews with the selected Yakan oral performers and youth in Basilan, Philippines, the study found that traditional stories and songs are primarily shared through informal gatherings and special occasions, and are highly valued as a means of preserving cultural heritage, expressing cultural identity and values, and fostering community cohesion. The study also identified several challenges to the preservation of Yakan oral tradition, including language shift, modernization, and a lack of institutional support. The results suggest that efforts to preserve and revitalize Yakan oral tradition should focus on promoting intergenerational transmission, supporting language revitalization efforts, and promoting institutional recognition and support for oral tradition. Overall, the study highlights the importance of oral tradition in maintaining cultural continuity and promoting community well-being among the Yakan people, and underscores the need for continued efforts to safeguard intangible cultural heritage in the Philippines and beyond.